The relationship of thermodynamic stability at a G x U recognition site to tRNA aminoacylation specificity. - Strazewski, P (1999)
The G x U pair at the third position in the acceptor helix of Escherichia coli tRNA(Ala) is critical for aminoacylation. The features that allow G x U recognition are likely to include direct interaction of alanyl-tRNA synthetase with distinctive atomic groups and indirect recognition of the structural and stability information encoded in the sequence of G x U and its immediate context. The present work investigates the thermodynamic stability and acceptor activity for a comprehensive set of variant RNAs with substitutions of the G x U pair of E. coli tRNA(Ala). The four RNAs with Watson-Crick substitutions had a lower acceptor activity and a higher stability relative to the G x U RNA. On the other hand, the RNAs with mispair substitutions had a lower stability, but either a higher or a lower acceptor activity. Thus, the entire set of variant RNAs does not exhibit a correlation between thermodynamic stability of the free, unbound tRNA and its acceptor activity. The substantial acceptor activity of tRNAs with particular mispair substitutions may be explained by their ability to assume the conformational preferences of alanyl-tRNA synthetase. Moreover, the G x U pair may provide a point of deformability for the substrate tRNA to adapt to the enzyme's active site.